Commercial Potential of Pelagic Sargassum spp. in Mexico - López Miranda, José Luis; Celis, Lourdes B.; Estévez, Miriam; Chávez, Valeria; van Tussenbroek, Brigitta I.; Uribe-Martínez, Abigail; Cuevas, Eduardo; Rosillo Pantoja, Izarelly; Masia, Luis; Cauich-Kantun, Citlali; Silva, Rodolfo (Frontiers in Marine Science, 2021)
The recent periodic influx of massive quantities of pelagic Sargassum spp. (sargasso) into the Caribbean has posed ecological, social and economic challenges to the region. Sustainable use of biomass is crucial to mitigate negative impacts of the beached algal masses. We review current uses of sargasso in Mexico, which include alginates, fucoidans and laminarin, biogas and bioethanol, animal feed, fertilizer, cosmetics, biofilters and construction materials. The commercialization potential of sargasso in the Mexican Caribbean is analysed using the SWOT technique (strengths, weaknesses, opportunities and threats). The unpredictability of the influx, in time and space of sargasso as it approaches the shore, as well as the lack of available technology, local infrastructure and regulations concerning sargasso are substantial, as well as establishing proper regulatory measures. For commercialization, beached sargasso can best be considered as “special waste” to establish regulations concerning its management. Lessons learned from Mexico may be applied elsewhere, although adapted to each specific context. In addition, mutual understanding of the constraints and possibilities of sargasso management of each country or territory may facilitate coordinated management of this transboundary macroalga bloom.